Positioning Human Rights of Older People in Long-term Care in Ireland- a Foucauldian Critical Discourse Analysis - Savolainen, Katja (Trinity College Dublin. School of Nursing & Midwifery. Discipline of Nursing, 2024)
Human rights have been positioned as basic principles which apply to everyone. However, there are frequent reports of breaches of human rights when older people access long-term care (LTC), with heightened debate during the COVID-19 pandemic. Fundamental rights, such as liberty, security, dignity, and autonomy, are impacted when older people enter LTC facilities (Cahill, 2018), and because of the intensified vulnerability of older people in this setting, they may face isolation and discrimination. When age-related issues in society become increasingly prominent, addressing them should be a priority. While various scandals and Health Information and Quality Authority (HIQA) reports have identified concerns, there is scant research which explores the concept and experience of human rights in LTC. Consequently, this study provides a unique understanding and illuminates the context of the human rights of older people in the LTC in Ireland using Foucauldian critical discourse analysis (FCDA). Aims and Objectives: The aims of the study were to examine how residents, family members, and staff discursively construct older people’s human rights in long-term care. Also to investigate knowledge of and language used by residents, family members and staff in relation to human rights of older people in long-term care in Ireland. Methodological Approach: Using FCDA, this study applied a qualitative design using semi-structured interviews with older people (residents), family members, and staff at four LTC facilities in Ireland. Ethical approval was granted by the Health Science Faculty Ethics Committee of Trinity Dublin College. Data were collected through individual semi-structured interviews (n=37) and a focus group (n=6). All interviews were audio-recorded, and transcription was undertaken by the researcher. Transcribed interview data and reflection notes were analysed using the 6-step FCDA framework developed by psychologist Carla Willig (2013). Findings: Forty-three individuals participated in the study: 17 older people, 11 family members, and 15 staff members. The findings demonstrated that the discursive positioning of the human rights of older people in LTC in Ireland was based on three main discourses: protection, conditional rights, and governance. All the discourses that emerged were interlinked and driven by ageism and paternalistic practices. In these practices, the decision-making of the older person is often limited, and human rights are limited or restricted. Power lies within the institution and is mediated by staff, which impacts the (non) ability of older people in LTC to claim rights. Conclusions: FCDA provided a unique way to investigate the intricacies of power-knowledge-discourse about how the human rights of older people were positioned in the LTC. Older people in LTC are positioned as ‘others’ (othering) (Rohleder in Teo, 2014), constituting a marginalised group that has lost their voice. A proxy voice is provided by family members who position themselves as advocates. Despite poor knowledge of human rights among staff, they unknowingly play an influential role in shaping the discourse surrounding the human rights of older people in LTC. Through their daily interactions and decision-making processes, staff wield disciplinary power and are an extension of the governmentality apparatus. This disciplinary power, as analysed through the Foucauldian framework, underscores the extent to which they can shape knowledge production in this context.
APPROVED
Keywords: Ageing; Human Rights; Long-term care; Residential care; Critical Discourse Analysis; Older People; Self-determination; Autonomy; Human rights approach to care; Foucault; Social construction